The Fundamentals of taxation - De Leon, Hector S. (Manila : Rex Book Store, 2000)
This book provide the reader with knowledge of the essentials of taxation, both national and local, with particular emphasis on basic principles, tax enforcement, and taxpayer's remedies.
Preface v -- Chapter I General principles -- Chapter II National taxation -- Chapter III Tax administration and procedure (in national taxation) -- Chapter IV Local taxation.
Keywords: TAXATION